Identifying the activities of physiotherapy practitioners through primary and secondary models of care provided in New South Wales emergency departments. (March 2022) - Maka, Katherine; Alkhouri, Hatem; Wong, Lilian; George, Laura; Walton, Anne; McCarthy, Sally
Abstract: Background: Following the introduction of the emergency department (ED) primary contact physiotherapy role, emergency physiotherapy models of care have evolved and are increasingly being adopted in the Australian ED. This has occurred due to growing ED patient demand and a need for greater workforce flexibility. Since introduction, there here has been limited evaluation of the scope of work physiotherapists are providing in Australian ED. Objectives: To identify the activities of ED physiotherapists provided through different models of care in NSW. Methods: Prospective observation study in 19 participating EDs conducted over 6 months between September 2014 and April 2015. Results: The study identified different models of care across participating hospitals where physiotherapists worked independently or in conjunction with a team through a referral service. The individual's scope of work was determined by organisational policy, culture, individual competence, knowledge and skills, and varied significantly between sites. Conclusions: These findings could guide both ED work flow and the development of multidisciplinary workforce structures to improve the utilisation of the physiotherapy service in EDs. This will allow for better service levels in hospitals, better access for patients and better use of resources.